In vitro study on the activity of essential oil and methanolic extract from Algerian Nigella sativa L. Seeds on the growth kinetics of micro-organisms isolated from the buccal cavities of periodontal patients - Fatima Zohra Kiari; Boumediene Meddah; Aicha Tir Touil Meddah (Saudi Dental Journal)
An in vitro evaluation of the antimicrobial activity of essential oil (EO) and methanol extract (ME) from Algerian Nigella sativa L. seeds against microbial strains isolated from the oral cavities of periodontal patients was performed. Twelve Gram-positive bacteria, eleven Gram-negative bacteria and three microscopic fungi strains were isolated and identified. The antimicrobial activities of EO and ME were tested against Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pneumoniae, Enterococcus faecalis, Klebsiella pneumoniae, Proteus sp., Acinetobacter baumannii/calcoaceticus, Porphyromonas sp., Veillonella sp., Candida sp. and Saccharomyces sp.. The total polyphenol and flavonoids contents of ME were higher than those of EO. Thin layer chromatography showed that catechin, gallic acid and quercetin were most likely present in the extracts. Fourier transform infrared spectrometry analysis (FT-IR) indicated the presence of bands from the CO groups of acids, alcohols, phenols, and ethers and the CO band of aldehydes. Analysis of the antimicrobial activity of N. sativa extracts obtained by the microdilution method showed excellent bactericidal activity of the essential oil and moderate efficiency of the ME against all the microbes tested. Staphylococcus epidermidis and Porphyromonas sp. were the most sensitive to EO (minimum bactericidal concentration (MBC): 16,500 μg/ml) at 48 h of incubation and, 125,000 μg/ml of ME was the most active against all the microbes tested. However, after18 or 24 h, this efficiency was decreased in some strains. In addition, Saccharomyces sp. and Candida albicans were more sensitive to EO than ME during the incubation, while this efficiency was clearly not visible with the agar well method, and most microbes tested presented remarkable resistance to these extracts. Keywords: Periodontal disease, Nigella sativa L. essential oil, Methanol extract, Bactericidal/fungicidal kinetics, Polyphenols, Flavonoids